Cell-free DNA derived from cancer cells facilitates tumor malignancy through Toll-like receptor 9 signaling-triggered interleukin-8 secretion in colorectal cancer. (15th September 2018) - Niu, Zhengchuan; Tang, Wentao; Liu, Tianyu; Xu, Pingping; Zhu, Dexiang; Ji, Meiling; Huang, Wenbai; Ren, Li; Wei, Ye; Xu, Jianmin
Abstract: Circulating cell-free DNA (cfDNA) has become a potential diagnostic and prognostic biomarker for colorectal cancer (CRC). In non-cancerous diseases, it has been confirmed that cfDNA can be recognized by Toll-like receptor 9 (TLR9), leading to a significant biological change. Nevertheless, the biological significance of cfDNA and its relationship with TLR9 in tumor malignancy is still unclear. Therefore, the purpose of this study is to explore the biological role of cfDNA in colorectal cancer (CRC). The expression of TLR9 was measured in different CRC cell lines and cancerous samples by RT-PCR or immunohistochemistry, which showed that high expression of TLR9 was significantly correlated with the tumor metastasis, advanced TNM stage and poor prognosis of patients. Then, cfDNA was obtained from fluorouracil (5FU)-induced apoptotic cancer cells in vitro and transfection techniques were used to transfect siRNA and cDNA plasmid for TLR9. Cancer cells were stimulated using isolated cfDNA fragments, and results showed that cfDNA could promote colorectal cancer cell proliferation via TLR9. Meanwhile, we demonstrated that the cfDNA binding to TLR9 could facilitate cell migration and invasion. Finally, we demonstrated that cfDNA initiated downstream TLR9-MyD88 signaling and induced robust release of chemokine interleukin 8 (IL-8), which helped to elucidate the mechanisms underlying these phenomena. Our data suggest that cancer cell-derived cfDNA contributes to cancer progression through activation of TLR9-MyD88 signaling and IL-8 secretion in CRC. These findings provide a novel perspective for understanding of tumor progression and provoke a potential therapeutic target for CRC treatment.